ISOLASI PROTEIN DARI AIR DANGKE - Andi Sukainah (HomeEC, 2009)
The aim of this research was to identify the hydrolize temperature (90˚C, 100˚C), HCl concentration (3M, 4M), and hidrolysis time (8h, 10h) to isolate protein from dangke’s water. The research found the optimum temperature was  90˚C with HCl concentration 4M, and hidolysis time of 10 hours.Key words: Air dangke, Protein, Hidrolisys.